COMO PLANEJAR E ELABORAR OBJETOS DE APRENDIZAGEM - Soares, Carine G. T.; Piva, Cláudia; Fritzen, Cledison E.; Michael, Danieli; Gonçalves, Marcia F.; Eickhoff, Fernando; Prediger, Reneo P. (Salão do Conhecimento, 2013)
Resumo